Strategi Peningkatan ZIS Pada Baitul Mal Kota Subulussalam Berdasarkan Qanun Nomor 19 Tahun 2010 - Rizky Ananda Aulia (Yayasan Rahmat Islamiyah, 2022)
This study aims to determine the ZIS acceptance at Baitul Mall in Subulussalam City in increasing the economy of ZIS recipients in Subulussalam City and to determine the strategy for increasing ZIS acceptance at Baitul Mal Subulussalam City based on Qanun Number 19 of 2010. The method used in this study is a qualitative descriptive method. The results of this study indicate that the Baitul Mal strategy of the city of Subulussalam has succeeded in increasing the number of receipts and distribution of ZIS starting from the implementation of offline strategies such as direct debriefing to the community or amil and online strategies such as utilizing social media Facebook, Instagram, Twitter and Websites in disseminating activities and conveying information. ZIS da'wah in 2019 to date. The influence of the distribution of ZIS funds on the improvement of the mustahik economy provides many improvements in which every poor community who receives Baitul Mal assistance is not only given free of charge, but is also given direct empowerment and guidance so that they can process the aid funds as well as possible for productive purposes. Thus changing the life status of those who were previously unable to pay zakat to be able to pay zakat from the results of their efforts which still exist today.